Hemorrhagic Epidermoid Cyst in Cerebellar Vermis: Case Report and Review of the Literature - Kozák, Ján; Šurkala, Jozef; Novotný, Martin; Švajdler, Marián (Journal of Neurological Surgery Reports, 2021)
Intracranial epidermoid cysts are slow growing congenital avascular neoplasms that spread across the basal surface of the brain. They most commonly occur in the paramedial region in the cerebellopontine angle and the parasellar region. Despite its generally benign nature, sporadically they can be accompanied with hemorrhage or very rarely undergo malignant transformation. The authors present a case report of a patient with a hemorrhagic vermian epidermoid cyst and a review of all published similar cases.
Keywords: epidermoid cyst; hemorrhagic epidermoid cyst; vermian epidermoid cyst; midline posterior fossa